Perspektif Pasien dengan Perlindungan Sosial Kesehatan tentang Peran Advokasi Perawat di Ruang Rawat Inap Kelas III Rumah Sakit Paru Jember (Nurse's Advocation Role in Patients With Social Health Insurance in Class III Inpatient Wards Paru Hospital Jember - Suyanti Suyanti; Nurfika Asmaningrum; Anisah Ardiana (Pustaka Kesehatan, 2014)
Various reports about service quality to social health insurance (Jamkesmas) participants pointed out that the given service to social health insurance was not compatible with the program’s purpose. As health professionals whom always keep patients company, nurses are required to be able to give primary care to all patients. Advocacy is one of nurse’s roles, in carrying out this role, nurses are helping patients making decision instead of making the decision for patients. This study is a qualitative study with phenomenological approach. Samples are acquired by purposive sampling method with the result 4 samples out of population. Data was obtained by interview using an interview guide as well as field notes. This data was analyzed with Colaizzi method. Results of study give rise to ten research themes which conclude a description of the particular goals. Those themes are the role of nurses in the inpatient admission procedure, provide information about the procedures of action, provide a suitable environment to the condition of the patient, assisting other health professionals, accompany the patient to undergo a medical examination, the type of actions taken, the role of nurses as patient managers, the nurse's role in planning after discharge, and JAMKESMAS service system. The nurses as care giver in Paru Hospital Jember should consider to the advocation role in all their actions. Keywords : patients’ perception, nurse advocation role